2018
DOI: 10.3390/molecules23051139
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Phenolic Compounds and Antioxidant Activity of 12 Cruciferous Vegetables

Abstract: The phenolic profiles of 12 cruciferous vegetables (pakchoi, choysum, Chinese cabbage, kailan, Brussels sprout, cabbage, cauliflower, broccoli, rocket salad, red cherry radish, daikon radish, and watercress) were studied with UHPLC-MS/MS. Antioxidant activity and total phenolic content (TPC) were also evaluated. A total of 74 phenolic compounds were identified, including 16 hydroxycinnamic acids and derivatives, and 58 flavonoids and derivatives. The main flavonoids identified were glycosylated quercetin, kaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 28 publications
5
82
1
Order By: Relevance
“…This shows that phenolic compounds, especially flavonoids, are the main compounds responsible for the antioxidant activity. Similar correlations were obtained in the study by Li et al (2018) with 12 cruciferous vegetables. Chihoub et al (2019) in their study with 80% of hydroethanolic extract from R. sativus L. leaves concluded that the phenolic compounds are strongly correlated to the antioxidant and the antimicrobial activity.…”
Section: Correlation Analyzesupporting
confidence: 87%
“…This shows that phenolic compounds, especially flavonoids, are the main compounds responsible for the antioxidant activity. Similar correlations were obtained in the study by Li et al (2018) with 12 cruciferous vegetables. Chihoub et al (2019) in their study with 80% of hydroethanolic extract from R. sativus L. leaves concluded that the phenolic compounds are strongly correlated to the antioxidant and the antimicrobial activity.…”
Section: Correlation Analyzesupporting
confidence: 87%
“…HPLC-PDA-ESI-MS analysis showed that the extracts contain derivatives of the flavonols quercetin, kaempferol, and isorhamnetin, and of the hydroxycinnamic acids sinapic acid and ferulic acid, which are conjugated with sugar moieties or hydroxycinnamic acids. These types of compounds are very common in Brassica species [5,[25][26][27][28][29][30]. Both flavonol glycosides and hydroxycinnamic esters have been reported to possess antioxidant activity [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, kaempferol, isorhamnetin, and cyanidin are the most representative flavonols in these species, but their qualitative and quantitative profiles vary significantly among species. For example, cauliflower main phenolic compounds are quercetin aglycon and catechins, but in white cabbage, the main compound are kaempferol glucosides and epicatechins [11,12]. The phenolic profile can also vary within the same plant species according to the plant organ being studied; for example, cruciferous sprouts can contain from 2 to 10 times more phenolic compound when compared with roots and inflorescences, which are the most common plant organ consumed [13].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The most common in this species are ferulic acid, sinapic acid, caffeic acid, and p-coumaric acid, but as occur with flavonols, this varies significantly according to the plant species considered. For example, sinapic acid is the main hydroxycinnamic acid present in rocket salad but is absent in red cherry and daikon radishes [11]. Another example of this considerable variation among species is ferulic acid, which represents the main hydroxycinnamic acid for red cabbage but is absent in radish and rocket leaves [12].…”
Section: Phenolic Compoundsmentioning
confidence: 99%